Estrategias en torno a las formas de apropiación y organización del espacio en un “barrio de migrantes” de la ciudad de Córdoba, Argentina - Magliano, María José; Perissinotti, María Victoria; Zenklusen, Denise (El Colegio de México A.C., 2014)
This work seeks to explore the strategies for appropriating and organizing the space establishedby Peruvian families in a “migrant neighborhood” in the city of Córdoba,Argentina. This neighborhood on the outskirts of the city, known as Los Artesanos, beganto be consolidated in 2009, following the settlement of a large number of migrant familieswho became pioneering residents. They were mainly Peruvians, though they alsoincluded Bolivian, Paraguayan and Argentinian families. This analysis reflects on thevarious survival strategies implemented by migrant families in contexts of social exclusionand inequality. To this end, it has implemented a qualitative methodology involvingparticipant observation and in-depth interviews of Peruvian men and women living inthe neighborhood at the time of the study.